Energy efficient copy distributing status aware routing mechanism in opportunistic network - Da-peng WU; Si-long FAN; GPu-ning ZHAN; Yi LV; Ru-yan WANG (Tongxin xuebao)
In opportunistic network, the relation between the node energy and message spreading degree is tradeoff. As a result, the network performance can be dramatically improved in limited resource scenarios by an effective routing me-chanism considering the node energy and copy status. Both the message spreading degree and node residual energy were taken into consideration, and then combined with the e probability predicting methods, an energy efficient copy distributing status aware routing mechanism was proposed, which could be used to choose the relay nodes reasonably. Numerical results show that the overhead can be reduced efficiently, and the message delivery ratio and latency can also be optimized.